2010
DOI: 10.1001/archinternmed.2010.356
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Association Between Depression and Type 2 Diabetes Mellitus in Women

Abstract: Background Although it has been hypothesized that the diabetes-depression relation is bidirectional, few studies have addressed this hypothesis in a prospective setting. Methods A total of 65381 women aged 50–75 years in 1996 were followed until 2006. Clinical depression was defined as having diagnosed depression or using antidepressants, and depressed mood was defined as having clinical depression or severe depressive symptomatology, i.e., a Mental Health Index (MHI-5) score ≤52. Self-reported type 2 diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
279
5
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 350 publications
(302 citation statements)
references
References 35 publications
9
279
5
9
Order By: Relevance
“…The increased prevalence of diabetes mellitus is associated with considerable morbidity and mortality with significant economic cost. Studies 10,11 have shown a bidirectional relationship between DM and MDD with increased psychological distress and physical complications where they co-exist. Both conditions separately and as co-morbidities are common in our environment.…”
Section: Introductionmentioning
confidence: 99%
“…The increased prevalence of diabetes mellitus is associated with considerable morbidity and mortality with significant economic cost. Studies 10,11 have shown a bidirectional relationship between DM and MDD with increased psychological distress and physical complications where they co-exist. Both conditions separately and as co-morbidities are common in our environment.…”
Section: Introductionmentioning
confidence: 99%
“…Depression increases the risk of developing T2D by 37% [22], and T2D seems to double the risk of developing depression [23], and there appears to be a bidirectional association between depression and T2D in women [24]. It is plausible that some T2D patients who are treated with metformin also suffer from depression and consequently ingest SJW concomitantly.…”
Section: Introductionmentioning
confidence: 99%
“…Exemplarisch sei der Diabetes mellitus genannt. Es liegen klare Evidenzen vor, wonach der Diabetes einerseits einen Risikofaktor für Depressionen darstellt [9] und sich andererseits bei depressiven Patienten im Krankheitsverlauf gehäuft verschiedene somatische Erkrankungen manifestieren, darunter auch der Diabetes mellitus [10].…”
Section: Depression Im Alterunclassified